The Effectiveness of Galltrap Compared to Commercial Fly Trap - Bilham Ramadhan; Agus Kharmayana Rubaya; Sarjito Eko Windarso; Rizki Amalia (Universitas Ahmad Dahlan, 2025)
Background: Synanthropic flies such as Musca domestica are capable of transmitting pathogens that cause diseases in humans, including diarrhea, cholera and dysentery. One effective method for controlling adult flies is the use of baited fly traps. The Ranch Fly Trap is a widely used commercial trap but has drawbacks such as being difficult to clean and relatively expensive. Galltrap was developed as an alternative made from disposable gallon containers (5L water bottles), offering a more economical, easy-to-use, and environmentally friendly option. Method: This research was an experimental study with a post-test only control group design, comparing Galltrap (experimental group) and Ranch Fly Trap (control group). Data collection was carried out over 16 repetitions at a poultry farm in Karanganjir, Sleman, in May 2025. Data were analyzed using an Independent Samples T-Test with significance level (α) = 0.05. Results: A total of 1,108 flies were trapped during the study, with 699 caught by Galltrap and 409 by Ranch Fly Trap. The average number of flies caught per day was 43.7 for Galltrap and 25.6 for Ranch Fly Trap. The T-test revealed a significant difference (p = 0.025), indicating that Galltrap was more effective, with a 71% higher daily catch rate compared to the Ranch Fly Trap. Conclusion: Galltrap demonstrated significantly greater effectiveness in capturing adult flies and offers a promising, low-cost solution for vector control in resource-limited settings.